Тератогенный эффект зерна овса из района, пострадавшего от аварии на Чернобыльской атомной электростанции - Бандажевский, Ю.И.; Дубовая, Н.Ф.; Швартау, В.В.; Михальская, Л.Н. (Фактори експериментальної еволюції організмів, 2014)
Aim. The aim of this paper was to study the influence of a food factor – oats obtained from an area contaminated with radioactive elements as a result of the Chernobyl accident on the course of pregnancy and development of embryos of laboratory animals – Syrian hamsters. Methods. Physiological, morphological (embryological), radiometric, physico-chemical, mathematical and statistical. Results. Oats grown in the area affected by the Chernobyl accident were found to contain increased amounts of radionuclides Cs-137 and Sr-90, as well as chemical elements Ba, Sr, Mn in comparison with the control (two times and more). Female Syrian hamsters in the experimental and control groups received the relevant oats as part of their diet from the moment of fertilization. The termination of pregnancy at the preimplantation stage was stated in 43.3 % of all cases of fertilization (in the control group – in 23.8 % of cases). The physiological course of pregnancy was recorded in 35.3 % of all pregnancies (in the control group – in 68.7 % of all pregnancies). Birth defects were detected in 41.2 % of all pregnancies (in the control group – in 12.5 % of all pregnancies, p < 0.05). Conclusions. This study shows a real danger to human health foods grown after 25 years on the area affected by theChernobyl nuclear power plant. Needed to evaluate the role of radiation-chemical factors in the contaminated areas in the human reproductive losses.